Innowacyjność sieci franczyzowych - Agnieszka Świętek (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, 2012)
A lasting success of business activities regardless of their location, nature, size and industry isnow dependent on the degree of innovation. Innovation is a way for modern enterprises to survive in thechanging market, and a response to customer needs, including their formation, but also seeking waysto develop the internal businesses, particularly in its organization and ideas. Innovation today cannotbe limited to the creation of new technological solutions, and then their implementation into industrialproduction. A particular kind of a modern business model, which has been recently developing inPoland and which is an example of an innovative organization in many fields, is the franchise, the focusof this article.In the article, the principles of operation and the current state of development of franchise networksin Poland is explained, and then the innovative features of franchise business in general, resultingfrom franchise agreements, are analyzed. In the final part of the article, examples of innovations arepresented: technological, market and organizational innovations, used in various franchise industries.In the article, the author also pays attention to the unique character of the franchise system, basedon assistance and transfer of know-how to its franchisees by the entrepreneur, which reduces therisk arising from the start-up of new economic activity, and affects the fast and multi-dimensionaldevelopment of franchise networks.